Public health initiatives from hospitalized patients with COVID-19, China - Chenkai Zhao; Yueqin Xu; Xu Zhang; Yaping Zhong; Li Long; Wenzhi Zhan; Tingting Xu; Chen Zhan; Yuehan Chen; Jinghai Zhu; Wei Xiao; Miao He (Elsevier, 2020)
Background: Since December 2019, when it first occurred in Wuhan, China, coronavirus disease 2019 (COVID-19) has spread rapidly worldwide via human-to-human transmission. We aimed to describe the epidemiological and demographic features of COVID-19 outside Wuhan. Methods: A single-center case series of 136 consecutive (from January 16 to February 17, 2020) patients with confirmed COVID-19 hospitalized in The First People's Hospital of Jingzhou, China, was retrospectively analyzed. Outcomes were followed up until February 19, 2020. Results: Of the 136 patients (median age, 49 years; interquartile range [IQR], 33-63 years; range, 0.3-83 years), 91 (67%) had been to Wuhan or contacted persons from Wuhan. Forty-five (33.1%) were familial clusters. The median incubation period was 6 days (IQR: 4-11 days). All children had an exact exposure history, family members with COVID-19, and "Mild/Moderate" symptoms at admission. Among the 64 elderly patients, 14 (21.9%) had no exposure history, and 43 (67.2%) had a chronic illness. All 11 (8.1%) "Severe/very severe" illness at onset cases and 5 (3.7%) fatal cases were elderly patients. The duration from symptom onset to admission was positively correlated with the duration from symptom onset to endpoint. Overall, patients with a longer incubation period had more severe outcomes. Conclusion: As high-risk susceptible groups, strong protection should be implemented for children and the elderly. Universal screening should be performed for people with a clear exposure history, even lacking apparent symptoms. Given the rapid progression of COVID-19, people should be admitted quickly following symptom onset.